Cross-domain interactions confer stability to benthic biofilms in proglacial streams - Busi, Susheel Bhanu; Peter, Hannes; Brandani, Jade; Kohler, Tyler J.; Fodelianakis, Stilianos; Pramateftaki, Paraskevi; Bourquin, Massimo; Michoud, Grégoire; Ezzat, Leïla; Lane, Stuart; Wilmes, Paul; Battin, Tom J. (Frontiers in Microbiomes, 2024)
Cross-domain interactions are an integral part of the success of biofilms in natural environments but remain poorly understood. Here, we describe cross-domain interactions in stream biofilms draining proglacial floodplains in the Swiss Alps. These streams, as a consequence of the retreat of glaciers, are characterised by multiple environmental gradients and perturbations (e.g., changes in channel geomorphology, discharge) that depend on the time since deglaciation. We evaluate co-occurrence of bacteria and eukaryotic communities along streams and show that key community members have disproportionate effects on the stability of community networks. The topology of the networks, here quantified as the arrangement of the constituent nodes formed by specific taxa, was independent of stream type and their apparent environmental stability. However, network stability against fragmentation was higher in the streams draining proglacial terrain that was more recently deglaciated. We find that bacteria, eukaryotic photoautotrophs, and fungi are central to the stability of these networks, which fragment upon the removal of both pro- and eukaryotic taxa. Key taxa are not always abundant, suggesting an underlying functional component to their contributions. Thus, we show that there is a key role played by individual taxa in determining microbial community stability of glacier-fed streams.